Mechanism for managing innovative potential at textile industry enterprises in the regions - Khosilov Shavkat Bekmurodovich (THE INNOVATION ECONOMY, 2026)
We know that increasing the innovative potential and activity of industrial enterprises is the main task of the ongoing consistent state policy for the sustainable and balanced development of the national economy, its strong position in the world market, and further improvement of the living standards and well-being of the population. This requires the formation of industrial enterprises that can withstand any process changes and quickly adapt to the requirements of the domestic and foreign markets in a context of increasing globalization of the world economy. Therefore, one of the main problems of the future development of the economy of Uzbekistan is the formation of a competitive and efficient innovative economy in the context of globalization. Achieving such results is achieved through the modernization and technical renewal of leading sectors and departments of the economy, the development of the training of highly qualified specialists and scientific personnel, and the formation of an intellectual property market, based on the use of high-tech scientific production